Adoption of IFRS in an emerging market: the Chilean case. Issue 4 (2nd November 2015) - Espinosa, Christian; Maquieira, Carlos; Diaz, Fernando; Abarca, Allyson
Abstract : Purpose: The purpose of this paper is to analyze the impact triggered by adopting International Financial Reporting Standards (IFRS) in South America. In order to do this, the case of Chile is considered, as it was the first country in the region to adopt IFRS in full form from 2009. Design/methodology/approach: The authors analyze a sample of 43 Chilean companies. The analysis has two stages. First, the authors analyze if the adoption of IFRS in Chile produced a statistically significant change in the main financial indicators. Then, the authors analyze the market reaction to the announcement of the adoption and implementation of IFRS, by doing an event study. Findings: The authors found that adopting IFRS in Chile produced a statistically significant change in the main financial indicators, except for in leverage and Price-Earnings Ratios. As for the main accounts of the financial statements, the authors found significant differences, with the exception of inventories and current assets. However, after assessing the market reaction to the announcement of the adoption and implementation of IFRS, by studying the events, the authors report neither reward nor punishment by the market. Originality/value: This paper pioneers the analysis of the impact triggered by adopting IFRS in South America. The authors results apply not only to Chile but also to a number of South American countries since many of these countries share similar characteristics with Chile. Abstract : Propósito: Nosotros analizamos el impacto provocado por la adopción de las Normas Internacionales de Información Financiera (IFRS) en América del Sur. Para ello consideramos a Chile, porque fue el primer país de la región en adoptar IFRS en forma completa a partir de 2009. Diseño/metodología/enfoque: Nosotros analizamos una muestra de 43 empresas chilenas. Nuestro análisis tiene dos etapas. En primer lugar, analizamos si la adopción de IFRS en Chile produjo un cambio estadísticamente significativo en los principales indicadores financieros. Luego, analizamos la reacción del mercado ante el anuncio de la adopción IFRS, mediante un estudio de eventos. Resultados: Encontramos que la adopción de IFRS en Chile produjo un cambio estadísticamente significativo en los principales indicadores financieros, a excepción de los ratios de apalancamiento y precio-beneficio. Además, encontramos diferencias significativas en las cuentas de los estados financieros, con la excepción de inventarios y activos circulantes. Por otra parte, después de evaluar la reacción del mercado ante el anuncio de la adopción de IFRS, mediante un estudio de eventos, no encontramos un premio ni un castigo por parte del mercado. Originalidad/valor: Somos pioneros en analizar el impacto provocado por la adopción de IFRS en América del Sur. Nuestros resultados se aplican no sólo a Chile, sino también a una serie de países de América del Sur, ya que muchos de estos países tienen con Chile similares características.